Subarachnoid Block Anesthesia as a Predictor of Perioperative Hypothermia in Cesarean Deliveries: A Clinical Study - Hastuti, Apriyani; Kurniawan, Ardhiles Wahyu; Rinanda, Nazri (STIKep PPNI Jawa Barat, 2025)
Background: Hypothermia, defined as a decrease in core body temperature below normal levels, is a common perioperative complication in patients undergoing surgical procedures, including cesarean section (CS). Subarachnoid Block (SAB) anesthesia has been identified as a contributing factor due to its thermoregulatory effects. Objective: This study aimed to evaluate the impact of SAB regional anesthesia on the occurrence of perioperative hypothermia in patients undergoing cesarean section. Methods: A pre-experimental study with a pretest-posttest design was conducted involving 60 cesarean section patients receiving SAB anesthesia at Al Fuadi General Hospital, Binjai. Body temperature measurements were taken before and after SAB administration. Data were analyzed using paired sample t-tests. Results: Prior to the administration of SAB anesthesia, the majority of patients (91.7%) exhibited normal body temperature, with a mean pretest temperature of 36.8°C (±0.3172). Following SAB administration, all patients (100%) developed hypothermia, with a mean posttest body temperature of 34.9°C (±0.4873), reflecting an average temperature decrease of 1.9°C. Statistical analysis indicated a significant effect of SAB anesthesia on the incidence of perioperative hypothermia (p = 0.000, p < 0.05). Conclusion: The administration of SAB regional anesthesia significantly increases the risk of perioperative hypothermia in cesarean section patients. Preventive strategies in clinical practice should include continuous monitoring of patient body temperature before, during, and after SAB administration to enable early detection and intervention, thereby reducing hypothermia-related complications.